Physical Activity and Its Association with Non-Communicable Diseases: Findings of A Population-Based Cross-Sectional Study in Bangladesh (Journal of Preventive and Social Medicine, 2026)
Background: Low physical activity is a leading risk factor for non-communicable diseases (NCDs). The present study aimed to assess physical activity and its association with NCDs in the context of Bangladesh.Methods: The study was a population-based cross-sectional study. We used the data generated by the country-wide survey conducted in Bangladesh in 2018. The survey was conducted using 496 primary sampling units developed by the Bangladesh Bureau of Statistics. Following the step-wise approach of the World Health Organization, the survey enrolled 8185 participants aged 18-69 years using a multi-stage sampling technique. The study conducted a face-to-face interview with Global Physical Activity Questionnaire to collect data on physical activity.Results: The average duration of physical activity was 244.8 minutes per day, while the median duration was 128.6 minutes. The prevalence of low physical activity was 12.6%, and it was higher among the participants aged 55-69 years (19.5%), women (14.7%), and urban dwellers (14.3%). Low physical activity was also higher (17.7%) among the participants with more than secondary level education. Participants with low physical activity were 1.36 times (OR=1.36, ρ=0.006) more likely to have diabetes mellitus, 1.53 times (OR=1.53, ρ